Enhanced Catalysis under 2D Silica: A CO Oxidation Study. Issue 19 (30th March 2021) - Eads, Calley N.; Boscoboinik, J. Anibal; Head, Ashley R.; Hunt, Adrian; Waluyo, Iradwikanari; Stacchiola, Dario J.; Tenney, Samuel A.
Abstract: Interfacially confined microenvironments have recently gained attention in catalysis, as they can be used to modulate reaction chemistry. The emergence of a 2D nanospace at the interface between a 2D material and its support can promote varying kinetic and energetic schemes based on molecular level confinement effects imposed in this reduced volume. We report on the use of a 2D oxide cover, bilayer silica, on catalytically active Pd(111) undergoing the CO oxidation reaction. We "uncover" mechanistic insights about the structure–activity relationship with and without a 2D silica overlayer using in situ IR and X‐ray spectroscopy and mass spectrometry methods. We find that the CO oxidation reaction on Pd(111) benefits from confinement effects imposed on surface adsorbates under 2D silica. This interaction results in a lower and more dispersed coverage of CO adsorbates with restricted CO adsorption geometries, which promote oxygen adsorption and lay the foundation for the formation of a reactive surface oxide that produces higher CO2 formation rates than Pd alone. Abstract : CO oxidation taking place under a 2D microporous silicon dioxide film demonstrates a ∼12 % enhancement in CO2 production by creating an interfacial microenvironment that fosters a higher coverage of reactive Pd surface oxide sites that are integral to CO2 conversion.